Effects of hook size and bait type on the size selectivity and short-time post-release mortality of a cyprinid fish (Cyprinus carpio L.) in recreational fisheries - Atessahin, Tuncay; Durrani, Omerhan (Elsevier, 2023)
A minimum legal length of 40 cm in recreational fisheries for the common carp (Cyprinus carpio) has been introduced in Turkiye and Czechia to prevent over-exploitation by anglers. This has resulted in more carp being released following capture, and possibly to increased losses of unharvested fish. This study was conducted to investigate the effect of hook size (4/0, 5/0, 6/0 & 7/0) and bait types (fish, corn kernels & dough) on the size of fish caught, catch rates, hooking location, dehooking time, bleeding (presence), and short-term post-release mortality. Angled fish were individually placed into a submerged cage for 1 h to monitor mortality. A total of 26 experimental fishing events, each event was divided into six angling sessions lasting 60 min each, were conducted at the Keban Dam Lake, Eastern Turkiye by three experienced anglers. Hook size influenced the size of captured fish but did not influence hooking location, dehooking time, bleeding (presence), and catch rates. Likewise, similar effects of bait type on hooking location, dehooking time, and bleeding (presence) were also recorded; however, in contrast to hook size, the bait type had a significant influence on fish catch rates and the catch efficiency of corn kernels was 2.1-3.4 times higher than the dough and fish baits. Furthermore, in contrast to the hook size, bait type had no significant influence on the size of fish caught. Smaller hook sizes were more likely to capture undersized fish, whereas larger hooks reduced the capture of undersized fish. Three out of 127 angled fish, caught by 4/0 and 5/0 hooks, experienced substantial bleeding and died within 1 h. The use of large hooks, e.g., > 5/0, is recommended to minimise the catch of undersized carp and mitigate hooking mortality.
Keywords: Angling; Carp; Catch -and -release; Hook selectivity; Hooking mortality; Recreational fisheries